Analisis Kelayakan Usahatani Pepaya Di Desa Tatelu Rondor Kecamatan Dimembe - Tidajoh, Revall Willy Ignatius; Talumingan, Celcius; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2024)
This research aims to determine and analyze the income and feasibility of papaya farming in Tatelu Rondor Village, Dimembe District, North Minahasa Regency. This research was carried out from June to August 2023. Sample selection in this study used purposive sampling method. The number of research respondents was 5 farmers. This research uses two types of data, namely primary and secondary data. The data analysis used is quantitative descriptive analysis using R/C Ratio analysis. The research results show that the revenue and cost ratio (R/C Ratio) of Bangkok papaya farming in Tatelu Rondor Village, Dimembe District is 1.86. The results of this analysis show that this farming is profitable and worth pursuing because the R/C Ratio value is > 1. The income of farmer respondents from Bangkok papaya farming in Tatelu Rondor Village is IDR7,572,020 with an average income of IDR1,514,404.